PENGARUH LATIHAN LARI SEGITIGA DAN LARI ZIG-ZAG TERHADAP PERKEMBANGAN FISIOLOGIS DAN KETERAMPILAN MOTORIK DALAM MENGGIRING BOLA PADA PEMAIN KLUB BARENG FC KOTA MALANG TAHUN 2024 - Novenrius Sini Timba, Frederiksen (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine the effect of triangle running and zig-zag running training on the physiological development and motor skills in dribbling the ball in Club Bareng FC Malang City players in 2024. This research uses an experimental method with a two group pretest-posttest design. The research subjects consisted of 30 players who were divided randomly into two experimental groups: group 1 (triangle running practice) and group 2 (zig-zag running practice). T-test analysis showed that both exercises had a positive effect on dribbling skills, with the triangle running exercise providing a greater improvement than the zig-zag running drill. These results indicate that agility and endurance training such as triangle running and zigzags can improve players' ability to dribble the ball, which in turn has the potential to improve their performance in matches.